Defective Nuclear Lamina in Aneuploidy and Carcinogenesis - CAPO-CHICHI, D. CALLINICE; SMITH, Elizabeth R.; Xu, Xiang-Xi (My University, 2018)
Aneuploidy, loss or gain of whole chromosomes, is a prominent feature of carcinomas, and is generally considered to play an important role in the initiation and progression of cancer. In high-grade serous ovarian cancer, the only common gene aberration is the p53 point mutation, though extensive genomic perturbation is common due to severe aneuploidy, which presents as a deviant karyotype. Several mechanisms for the development of aneuploidy in cancer cells have been recognized, including chromosomal non-disjunction during mitosis, centrosome amplification, and more recently, nuclear envelope rupture at interphase. Many cancer types including ovarian cancer have lost or reduced expression of Lamin A/C, a structural component of the lamina matrix that underlies the nuclear envelope in differentiated cells. Several recent studies suggest that a nuclear lamina defect caused by the loss or reduction of Lamin A/C leads to failure in cytokinesis and formation of tetraploid cells, transient nuclear envelope rupture, and formation of nuclear protrusions and micronuclei during the cell cycle gap phase. Thus, loss and reduction of Lamin A/C underlies the two common features of cancer-aberrations in nuclear morphology and aneuploidy. We discuss here and emphasize the newly recognized mechanism of chromosomal instability due to the rupture of a defective nuclear lamina, which may account for the rapid genomic changes in carcinogenesis.
Keywords: aneuploidy; lamin A/C; nuclear budding; nuclear deformation; nuclear envelope; nuclear lamina; nuclear morphology; ovarian cancer.